Compensation, Organizational Culture and Job Satisfaction In Affecting Employee Loyalty - Bagus Nyoman Kusuma Putra; I Wayan Gede Antok Setiawan Jodi; I Made Surya Prayoga (Journal of International Conference Proceedings (JICP), 2019)
Achieving the goals of an organization or company will be very important for companies to have quality and professional human resources. In general, human resources create, manage and manage all the existing development factors. Employee loyalty is determined by factors of compensation, organizational culture, and job satisfaction. The purpose of this study is to determine the effect of compensation, organizational culture, and job satisfaction on employee loyalty GO-JEK drivers in Bali. The method used is multiple linear regression analysis. The sampling technique used was simple random sampling with a Slovin formula of 99 respondents. The results showed that compensation, organizational culture and job satisfaction partially had a positive and significant effect on employee loyalty GO-JEK drivers in Bali